Design, Synthesis, and Application in OFET of a Quinoxaline-Based D-A Conjugated Polymer - Dai, Zhicheng; Zhang, Daohai; Zhang, Haichang (Frontiers in Chemistry, 2022)
A novel alternating donor–acceptor polymer PQ1 is designed and synthesized by palladium-catalyzed Stille coupling between quinoxaline as an electron-deficient unit and indacenodithiophene (IDT) as electron-rich groups. Polymer PQ1 presents not only a strong intramolecular charge transfer effect, which is beneficial for the charge transport within single molecules but also a narrow electrochemical band gap and a high highest occupied molecular orbital (HOMO) energy level. In addition, the optical absorption study indicates that the PQ1 film exhibits good aggregation, which is an advantage for the charge transport between neighboring molecules. As a consequence, PQ1 presents p-type semiconductor properties with a high hole mobility of up to 0.12 cm2 V−1 s−1. This study reveals the great potential of quinoxaline-type chromophores in constructing novel organic semiconductors.